2015
DOI: 10.1016/j.bbamem.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Design of new fluorescent cholesterol and ergosterol analogs: Insights from theory

Abstract: Cholesterol (Chol) and ergosterol (Erg) are abundant and important sterols in the plasma membrane of mammalian and yeast cells, respectively. The effects of Chol and Erg on membrane properties, as well as their intracellular transport, can be studied with use of fluorescence probes mimicking both sterols as closely as possible. In the search for new and efficient Chol and Erg probes, we use a combination of theoretical methods to explore a series of analogs. The optical properties of the analogs (i.e. excitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 91 publications
(28 reference statements)
4
31
0
Order By: Relevance
“…1, panels A and B in Wüstner, ). This is further supported by an only small increase in dipole moment of DHE during excitation (Smutzer et al ., ), a property which is preserved for polyene sterols with more double bonds, as we have shown previously by electronic structure calculations (Nåbo et al ., ). Accordingly, only low environmental sensitivity of emitted fluorescence is expected for polyene sterols.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…1, panels A and B in Wüstner, ). This is further supported by an only small increase in dipole moment of DHE during excitation (Smutzer et al ., ), a property which is preserved for polyene sterols with more double bonds, as we have shown previously by electronic structure calculations (Nåbo et al ., ). Accordingly, only low environmental sensitivity of emitted fluorescence is expected for polyene sterols.…”
Section: Resultsmentioning
confidence: 97%
“…In particular, it could be interesting to aim for introducing a fifth conjugated double bond to further shift the excitation and emission maxima into the visible range. Such a fifth double bond should be introduced between carbons 1 and 2 in ring A – any other position would require removing a methyl group which, according to our previously published results, would negatively influence the cholesterol‐mimicking properties of the probe (Nåbo et al ., ). Extending the conjugated system to five double bonds should also increase the relative stability of the enol tautomeric form due to an increased influence of the resonance effect.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some equivalent studies have also been carried out for biological systems, combining MD simulations and electronic structure calculations to determine the orientation of probes in a phospholipid membrane, [100,101] and in the context of designing fluorescent probes to mimic the alignment behaviour of biological molecules. [102] A further comparative study of five anthraquinone dyes proposed for use within guest-host systems has provided insights into structure-property relationships of the dyes. [103] Variations in dye colour have been rationalised in terms of the electronic properties of the dye substituents, and reported trends in absorption anisotropy have been rationalised in terms of TDM orientations and molecular aspect ratios, determined from the results of DFT and TD-DFT calculations.…”
Section: Rational Design Of Guest-host Systemsmentioning
confidence: 99%
“…However, spectroscopic charac- (about half the energy) and can thereby be used for live-cell imaging over extended periods of time [25,28]. Probe 25-OH-3a is inspired by our previous work on cholesterol probes [29,30]. Here, we also consider the keto form of this probe because we found that probe 3a can undergo keto-enol tautomerization [31], and this is probably also the case for 25-OH-3a.…”
Section: Page 5 Of 32mentioning
confidence: 99%